Pengaruh Kombinasi 2.4 D (Dichlorophenoxyacetic) dan BAP (Benzyl Amino Purine) pada Media MS (Murashige Skoog) Terhadap Induksi Kalus Tanaman Tebu (Saccharum officinarum L.) Varietas AAS Agribun - Fatahillah, Rizky; Rahmi, Hayatul; Saputro, Nurcahyo Widyodaru; Suhesti, Sri (UNIVERSITAS LABUHANBATU, 2024)
Sugarcane (Saccharum officinarum L.) is a plant that is used as the main ingredient in making sugar. Sugar consumption in Indonesia increases from year to year due to population growth. One of the efforts to provide superior seeds in a short time and in large quantities is through tissue culture. This study aims to determine the effect of a combination of 2,4 D (Dichlorophenoxyacetic) and BAP (Benzyl Amino Purine) and determine the best treatment. The research method used is an experimental method using a completely randomized design (CRD) combination with 3 replicates and 9 treatments consisting of: (A); 1 ppm 2,4 D + 0 ppm BAP (B); 2 ppm 2,4 D + 0 ppm BAP (C); 3 ppm 2,4 D + 0 ppm BAP (D); 1 ppm 2,4 D + 0.1 ppm BAP (E); 2 ppm 2,4 D + 0. 1 ppm BAP (F); 3 ppm 2,4 D + 0.1 ppm BAP (G); 1 ppm 2,4 D + 0.2 ppm BAP (H); 2 ppm 2,4 D + 0.2 ppm BAP (I); 3 ppm 2,4 D + 0.2 ppm BAP. The results showed that there was a significant effect of the combination of 2,4-D and BAP on the time of callus appearance and callus diameter in callus induction of Sugarcane (Saccharumofficinarum L.) variety AAS Agribun. The treatment of C (2,4-D 3 ppm + BAP 0 ppm) produces the highest percentage of live explants which is 100%, the fastest callus emergence time which is 15.67 hsi, the largest diameter which is 2.04 cm and the heaviest callus fresh weight with a value of 0.86 grams. Keywords: sugarcane, 2,4 D, BAP, callus induction